2021
DOI: 10.1186/s40623-020-01323-x
|View full text |Cite
|
Sign up to set email alerts
|

Focal mechanisms and the stress field in the aftershock area of the 2018 Hokkaido Eastern Iburi earthquake (MJMA = 6.7)

Abstract: The tectonic stress field was investigated in and around the aftershock area of the Hokkaido Eastern Iburi earthquake (MJMA = 6.7) occurred on 6 September 2018. We deployed 26 temporary seismic stations in the aftershock area for approximately 2 months and located 1785 aftershocks precisely. Among these aftershocks, 894 focal mechanism solutions were determined using the first-motion polarity of P wave from the temporary observation and the permanent seismic networks of Hokkaido University, Japan Meteorologica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…There are some studies on the 2018 Hokkaido Eastern Iburi earthquake. Susukida et al [12] investigated the tectonic stress field in and around the aftershock area of the earthquake and found that the reverse fault-type stress field was dominant in the aftershock area. Zhou et al [13] analyzed the mechanism of regional landslides and the stability and permanent displacement of slopes based on the effects of continuous heavy rainfall and seismic motion.…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies on the 2018 Hokkaido Eastern Iburi earthquake. Susukida et al [12] investigated the tectonic stress field in and around the aftershock area of the earthquake and found that the reverse fault-type stress field was dominant in the aftershock area. Zhou et al [13] analyzed the mechanism of regional landslides and the stability and permanent displacement of slopes based on the effects of continuous heavy rainfall and seismic motion.…”
Section: Introductionmentioning
confidence: 99%